PENGEMBANGAN BAHAN AJAR ETNOPEDAGOGI BERBASIS KEARIFAN LOKAL MASYARAKAT CIAMIS PADA MATA PELAJARAN IPAS KELAS IV - Nuralifah, Dea Aulia Nisrina; Anggit Merliana; Pidi Mohammad Setiadi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Social Studies is closely linked to local wisdom, as both emphasize cultural values and community life. In the development of IPAS learning in elementary schools, it is essential to provide teaching materials that integrate local culture and values. This study aims to explore the local wisdom of the Ciamis community based on cultural elements as an alternative learning resource for IPAS. The research employs the Educational Design Research (EDR) method, which includes the stages of Analysis and Exploration, Design Construction, and Evaluation and Reflection. The results of the validation by content and media experts indicate validity scores of 75% and 92%, respectively, which are categorized as valid. Therefore, the developed teaching material prototype is considered appropriate for use in classroom learning activities.